Culture and Cultural Entities - Toward a New Unity of Science - Margolis, Joseph. author. aut Link
XVI, 156 p.
Keywords: Culture and Cultural Entities provides an original philosophical analysis of the nature and explanation of cultural phenomena, with special attention to ontology and methodology. It addresses in depth such topics as: the relation between physical and biological nature and cultural phenomena; the analysis of intentionality; the nature and explanation of action; causality; causal explanation and the unity of science; theories of language; historicity; animal and human intelligence; psychological and social phenomena; technology and evolution. Its approach features a form of non-reductive materialism, examines a wide range of views, and is highly readable, making it suitable for professionals, advanced undergraduate and graduate students, and an informed general audience. A new chapter was added to give a sense of pertinent trends since the appearance of the first edition, particularly with respect to the history of philosophy, pragmatism, the unity of science, and evolution. The unity, scope, and simplicity of the theory are well-regarded.